Employee age and the impact on work engagement. Issue 5 (3rd July 2020) - Douglas, Stephanie; Roberts, Robin
Abstract : Purpose: Employee engagement studies are popular in contemporary research because of the complexity organizations face in nurturing the performance and productivity of multi-generations of workers. The purpose of this paper is to assess association of age and dimensions of work engagement. Design/methodology/approach: In total, 181 participants completed the Utrecht Work Engagement Scale (UWES) to measure work engagement including the dimensions of absorption, vigor and dedication as well as demographics. One-way ANOVA and post hoc tests were conducted to examine the relationship between age and work engagement. Findings: Employees 50 years of age and older were found to have statistically significant higher work engagement scores than the employees under the age of 50. Statistically significant scores were also found to be higher in absorption and dedication. Originality/value: The workforce is aging with older employees becoming larger populations in organizations. Understanding how age influences employee work engagement supports human capital management strategy within organizations. HR professionals can also use the findings to develop targeted employee engagement to leverage the dedication and talents of older employees.